Improvement of MGMP Chemistry Teacher Competency in 50-Kota Districts on OSN Preparing Students - Edi Nasra; Sri Benti Etika; Desy Kurniawaty; Bahrizal Bahrizal; Eka Yusmaita (Fakultas MIPA Universitas Negeri Padang, 2019)
Training in increasing the competence of MGMP Chemistry teachers in 50 City Regencies in preparing students for the National Science Olympiad (OSN). The activity began with filling out a questionnaire for the readiness of the teachers in the learning process and pre-test to see the initial abilities of the MGMP Chemistry teachers in the City 50 District. After training in strengthening chemical materials and discussing HOTS questions in the fields of Analytical Chemistry, Organic Chemistry, Inorganic Chemistry, Physical Chemistry and Biochemistry, a post test was conducted to evaluate the achievement of the objectives of the activity. From the questionnaire given at the beginning of the activity it can be concluded that in general the teachers were ready for learning even though they were not used to the HOTS questions of the Olympic type questions. This is directly proportional to the pre-test results with an average value of 3.625 (scale 10). After the training of the teachers there was a significant increase which was shown by the results of the post test with an average of 5.5 (scale 10). As an evaluation material, at the end of the activity the satisfaction questionnaire was distributed and the results obtained were an average of a questionnaire of 3.47 (scale 4). Generally teachers complain about the lack of training time so that the absorption of the material provided is quite low.